Pengaruh tata elemen fisik terhadap pola aktivitas pengunjung pada Taman Lila Ulangun di sempadan Sungai Oongan Denpasar - Wisesa, Putu Pradnya Teguh; Semarajaya, Cokorda Gede Alit; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2022)
The river border arrangement can be used as a place for public activities, which one is the Lila Ulangun Park on the Oongan River (tukad) border, Tonja Village, Denpasar. Previously, this area was an unorganized area that it had minimal activity. With the arrangement on this river border, indirectly invites people or visitors to do activities in here. Activities that occur in Lila Ulangun Park are related to physical element settings. This study aims to identify utilization activity patterns and the influence of the physical setting at Lila Ulangun Park. This study uses descriptive qualitative methods with data collection techniques by means of literature studies, interviews and field observations. The results of this study indicate that the intensity of visitors in the classification of time units looks different where the most activity occurs in the afternoon. From the research results, it was also found that there was a relation between activity and the physical setting of the park as well as the influence of activity. Shade in the form of shady trees, gazebo, accessibility, open space, and lighting are the most influential physical elements in safety and comfort in activities with different time contexts. Researchers provide recommendations in the form of facilities such as gazebos, shade trees, and lighting at several points of the room.